Fructose Syrup: A Biotechnology Asset - Rita de Cássia L. Figueiredo Ribeiro; Diego Sampaio Nascimento; Pedro Fernandes; Danyo Maia Lima; Sandra Aparecida de Assis (Food Technology and Biotechnology, 2011)
In response to the growing demand for the consumption of natural, healthy and low-calorie food, a large number of so-called alternative sugars has emerged since the early 80s, among them fructose. This sugar is a ketohexose, known as D-fructose or levulose, and is considered the sweetest sugar found in nature. Currently, fructose is mostly produced through the acid hydrolysis of sucrose, or through the multi-enzymatic hydrolysis of starch. Processes involving specific enzymes like inulinases, acting on widely available fructose polysaccharides such as inulin, have been studied as alternatives to the current approaches, in order to reduce time, complexity and costs involved in this process. Fructose syrup is used worldwide, mainly because of its sweetening power and functional properties. The present work aims to provide an overview of the properties of fructose and of the present and envisaged production processes, within the scope of a biotechnological approach.